Critical Discourse Analysis of International Media Framing of the Iran–United States Conflict - Nabila Shaini Putri; Farid Rizaldi; Fitra Aulia Simatupang; Indi Azizah Nailah; Muhammad Natsir (International Journal of Education and Literature, 2026)
A single paragraph, maximum 250 words. Abstract content must contain (1) an overview of the object of research, (2) problems, and research objectives, (3) proposed methods, (4) main findings and results and synthesis of main ideas, and (5) conclusions. In recent years, the Iran–United States conflict has not only unfolded within the geopolitical arena but has also been intensively constructed through international media framing that shapes how global audiences understand this reality. In the context of the digital information overflow, media no longer function merely as conveyors of facts; rather, they act as agents that construct meaning, evoke emotions, and shape the social perceptions of audiences. This study aims to analyze how international media framing constructs representations of the Iran–United States conflict and how audiences interpret such discourse within their social experiences. This research adopts a qualitative approach with a Critical Discourse Analysis (CDA) design. Data were collected through document analysis of 25 news articles from both Western and non-Western media, as well as exploratory interviews with nine participants from academic backgrounds. Data analysis was conducted using a thematic approach based on Norman Fairclough’s three-dimensional model. The findings reveal three main patterns: the construction of threat through media language, moral polarization that produces a dichotomy of “us versus them,” and the negotiation of meaning by audiences, which is reflective and not always linear. These findings indicate that audiences are not entirely passive; rather, they actively interpret and, at times, question media framing. Theoretically, this study extends Critical Discourse Analysis by incorporating the dimension of audience experience into the discursive process. Practically, it underscores the importance of critical media literacy in navigating the complexity of global information and opens avenues for further exploration of the relationship between discourse, power, and social experience.